1975
DOI: 10.1159/000178685
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Inhibition of Pineal Antigonadotrophic Activity in Male Rats

Abstract: The influence of subcutaneous implants of melatonin on reproductive organ growth in neonatally testosterone propionate-(TP)-treated, blinded rats was investigated. The testes and accessory sex organs of rats that were TP-treated and blinded grew significantly slower than those of intact control rats. Either treatment of animals with melatonin or pinealectomy partially restored growth of the reproductive organs. In that the effects of melatonin treatment were similar to those of pinealectomy in this experiment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1976
1976
1988
1988

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Previous studies of rats with pineal-mediated gonadal regression demonstrate that subcutaneous deposits of melatonin reversed the antigonadotrophic effects induced by the combination of blinding with anosmia (Chen & Reiter, 1980) or neonatal androgenization (Banks & Reiter, 1975). Melatonin pellets did reverse the effects of melatonin injections on relative testicular weight, supporting the hypothesis generated from data from rats and hamster that melatonin available as a pellet is counterantigonadotrophic.…”
Section: Discussionsupporting
confidence: 62%
“…Previous studies of rats with pineal-mediated gonadal regression demonstrate that subcutaneous deposits of melatonin reversed the antigonadotrophic effects induced by the combination of blinding with anosmia (Chen & Reiter, 1980) or neonatal androgenization (Banks & Reiter, 1975). Melatonin pellets did reverse the effects of melatonin injections on relative testicular weight, supporting the hypothesis generated from data from rats and hamster that melatonin available as a pellet is counterantigonadotrophic.…”
Section: Discussionsupporting
confidence: 62%
“…Melatonin (5-methoxy, N acetyl serotonin) the pineal hormone has been reported to influence gonadal activity in mammals depending upon the time, the mode of administration and the condition of the animals (Reiter, 1977(Reiter, , 1980Turek et al, 1975. It has a progonadal effect as well as an inhibitory role on reproduction (Banks et al, 1976;Hoffman, 1974;Reiter, 1973Reiter, , 1974Relkin, 1976;Wurtman et al, 1968). Chen et al(1980) have shown that the injection of melatonin in the morning prevents the antigonadal effects of evening injection of the same in hamsters.…”
mentioning
confidence: 99%
“…Also the amounts of synthetic MEL required to produce antigonadotropic effects are generally in mg dosages and various negative reports have been published [T h ieblo t, 1966a, 1966bT albot and R eiter, 1973/74;Ebels and Pr o p , 1965]. Indeed, it has been shown that certain types of treatment with MEL actually counteract pineal-induced gonadal atrophy [H o ffm a n, 1974;R eiter et al, 1974, 1975a, 1975b, 1975cBanks and R eiter, 1975], Recently, T am arkin and coworkers [1976] discovered that the antigonadotropic effects of synthetic MEL were dependent upon the time of injection. Thus, MEL may be antigonadotropic if given at the proper time during the light-dark cycle.…”
Section: New Look At Melatoninmentioning
confidence: 99%